Education in the Background of Artificial Intelligence - Yujie Shi (International Journal of Management and Education in Human Development, 2023)
Nursing vocational education is an important part of nursing education in China at the present stage. It plays a very important role in promoting the vigorous development of nursing and the education and training of higher nursing talents. Therefore, in order to promote the trained nurses to better meet the needs of medical development, China has also carried out innovative reform on the educational model of vocational nursing. The effect of vocational nursing education can directly affect the quality and specification of nursing talents. This paper summarizes the problems existing in the current nursing vocational education, and puts forward some methods, hoping to provide some references for promoting the vigorous development of nursing vocational education in China.